Dysbindin-1, BDNF, and GABAergic Transmission in Schizophrenia - Jun, Rachel; Zhang, Wen; Beacher, Nicholas J.; Zhang, Yan; Li, Yun; Lin, Da-Ting (Frontiers in Psychiatry, 2022)
Schizophrenia is a psychiatric disorder characterized by hallucinations, anhedonia, disordered thinking, and cognitive impairments. Both genetic and environmental factors contribute to schizophrenia. Dysbindin-1 (DTNBP1) and brain-derived neurotrophic factor (BDNF) are both genetic factors associated with schizophrenia. Mice lacking Dtnbp1 showed behavioral deficits similar to human patients suffering from schizophrenia. DTNBP1 plays important functions in synapse formation and maintenance, receptor trafficking, and neurotransmitter release. DTNBP1 is co-assembled with 7 other proteins into a large protein complex, known as the biogenesis of lysosome-related organelles complex-1 (BLOC-1). Large dense-core vesicles (LDCVs) are involved in the secretion of hormones and neuropeptides, including BDNF. BDNF plays important roles in neuronal development, survival, and synaptic plasticity. BDNF is also critical in maintaining GABAergic inhibitory transmission in the brain. Two studies independently showed that DTNBP1 mediated activity-dependent BDNF secretion to maintain inhibitory transmission. Imbalance of excitatory and inhibitory neural activities is thought to contribute to schizophrenia. In this mini-review, we will discuss a potential pathogenetic mechanism for schizophrenia involving DTNBP1, BDNF, and inhibitory transmission. We will also discuss how these processes are interrelated and associated with a higher risk of schizophrenia development.